Teaching Arabic as a second language: an evaluation of key word method effectiveness - Yaakub, Muhamadul Bakir (Universiti Teknologi Malaysia, 2007)
This study aims to examine the effectiveness and the practicality of the “key word method” in teaching and learning Arabic as a foreign language within the Malaysian secondary school curriculum. The method is designed to overcome the challenges of learning Arabic, so that they become motivated in achieving their learning target and become innovative in their learning activities. The issue here is whether a learning method is really on par with its learning function, such as developing a memory learning strategy by understanding the working of the brain. The study conducted an experiment to see whether the memory learning strategy would have an impact on learners in a controlled enviroment.